FREQUENCY AND CHARACTERISTICS OF SKIN CANCERS DIAGNOSED AT AYUB MEDICAL COLLEGE, ABBOTTABAD PAKISTAN FROM 1995-2003 - Ahmed, Ayesha; Alam, Mian Bilal; Khan, Waheed; Badar, Ahmed; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 2007)
Background: Our histopathology laboratory serves mountainous area of Hazara Division in Northern Pakistan. This study is an analysis of the records of skin cancers reported over a nine years period to develop local statistics about frequency and characteristics of skin cancers. Methods: Data from 1995-2003 record of cancers reported by Department of Pathology, Ayub Medical College, Abbottabad were analysed to calculate cumulative and year wise frequency of skin cancers and their major types. Frequency distribution with reference to gender and age was also calculated. Results: Skin cancers were 220 (1.04%) out of the total 21075 cancers recorded during this period. Squamous cell carcinoma was diagnosed in 118 (53.6%), Basal cell carcinoma in 88 (40%) and Malignant melanoma in 14 (6.4%) cases. The mean age for all skin cancers considered together was 58.75±15.21. Non Melanoma Skin Cancer (NMSC) were seen in all age groups (minimum 15, maximum 103 years), while no malignant melanoma patient was under 35 years of age. Gender difference in distribution was negligible with slight male preponderance (23:21). Malignant melanoma was significantly (p<0.05) more in males (71.4%), while distribution of both the types of NMSC was non-significantly in favour of males. We found no significant rise or fall in total skin cancers or any type of skin cancer in this 9 years period. Conclusions: At present the frequency of skin cancer is stable at around 1 % of total cancers reported at Ayub Medical College, reflecting a stable very low incidence rate of skin cancer in Hazara Division of Pakistan. Keywords: Skin Cancer, Malignant melanoma, Non melanoma Skin Cancer, Pakistan, Histopathology